遺伝子改変ゼブラフィッシュを用いた新規薬物治療法の開発 - 林, 由起子; 川原, 玄理 (日本薬理学会年会要旨集, 2021)
Zebrafish is an excellent animal model for human diseases due to its high genetic homology to human, and easy genetic manipulation. To monitor the expression of Muscle RING-finger protein-1 (MuRF1) gene, which is one of marker molecules of muscle atrophy, a transgenic zebrafish line was created with microinjection of murf1 promoter-EGFP cDNA construct using tol2 transposon system.During early development in the transgenic fish (murf1:EGFP) line, EGFP signals were observed in skeletal muscle and heart from 1 day post-fertilization (dpf). RT-PCR analysis confirmed that the murf1 gene expression was corresponded with EGFP expression after 1 dpf. In the adult transgenic fish, murf1 expression corresponding with EGFP were mainly observed in skeletal muscle and heart. Treatment with dexamethasone solution at 4 dpf for 24 hours induced up-regulation of EGFP expression in murf1:EGFP zebrafish. These results indicated that the murf1 expression could be monitored using the murf1:EGFP fish. Using the murf1:EGFP fish, we have screened 1,280 drugs to discovery chemicals to reduce the expression of zebrafish murf1, and five candidate chemicals were identified.Our murf1:EGFP fish line might be excellent tool to evaluate the expression of murf1 and is useful to therapeutic drug screening for muscle atrophy.